ASSESSMENT OF ELECTROCHEMICAL PROPERTIES OF A BIOGALVANIC SYSTEM FOR TISSUE CHARACTERISATION - Yo’lchiyev Mash’albek Erkinovich; Yo’lchiyeva Sevara Tojimatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract Bio galvanic characterization is a promising method for obtaining health-specific tissue information. However, there is a dearth of understanding in the literature regarding the underlying galvanic cell, electrode reactions and their controlling factors which limits the application of the technique. Our findings suggest that the prominent reaction at the cathode is that of oxygen-reduction, not hydrogen-evolution. Results indicate that cell potentials are influenced by the concentration of dissolved oxygen at low currents and maximum closed cell currents are limited by the rate of oxygen diffusion to the cathode. Characterized internal resistance values for the salt solutions did not correspond to theoretical values at the extremes of concentration (1.71 and 154 mM) due to electrode resistance and current limitation. Existing bio galvanic models do not consider these phenomena and should be improved to advance the technique and its practical application.